2001
DOI: 10.1086/322867
|View full text |Cite
|
Sign up to set email alerts
|

A Map of the Ionized Component of the Intermediate-Velocity Cloud Complex K

Abstract: The neutral and ionized gas generally trace each other quite well in the complex, but the detailed structure is not identical. In particular, the Ha emission peaks in brightness at slightly higher Galactic longitudes than corresponding 21 cm features. The ionized gas has a peak Ha intensity of 0.5 R, corresponding to an emission measure of 1.1 cm Ϫ6 pc. Structures in the complex are traced by WHAM down to about 0.1 R (0.2 cm Ϫ6 pc). Typical line widths of the Ha emission are ∼30 km s Ϫ1 , limiting temperatures… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 24 publications
2
34
0
Order By: Relevance
“…This result is similar to that for the intermediatevelocity clouds Complex K and Complex L, which have also been mapped in Hα with WHAM (Haffner et al 2001;Haffner 2005). In all three clouds, the presence of Hα and H i emission tend to track each other in corresponding sight lines, but there is no strong correlation between the Hα and H i intensities, with the exception of the tip of the Smith Cloud (blue "×" in Figure 2), which is the brightest portion in both Hα and H i.…”
Section: Discussion and Future Worksupporting
confidence: 86%
See 2 more Smart Citations
“…This result is similar to that for the intermediatevelocity clouds Complex K and Complex L, which have also been mapped in Hα with WHAM (Haffner et al 2001;Haffner 2005). In all three clouds, the presence of Hα and H i emission tend to track each other in corresponding sight lines, but there is no strong correlation between the Hα and H i intensities, with the exception of the tip of the Smith Cloud (blue "×" in Figure 2), which is the brightest portion in both Hα and H i.…”
Section: Discussion and Future Worksupporting
confidence: 86%
“…Typical Hα intensities for HVCs are 0.06-0.5 R (Tufte et al 1998;Haffner et al 2001;Weiner et al 2001Weiner et al , 2002Putman et al 2003;Haffner 2005); the intensities observed here for the Smith Cloud are in this range. The narrow range of Hα intensities for these clouds suggests that, like the WIM, all of these HVCs are ionized by a diffuse UV radiation field, not shocks or individual, local hot stars (see also Bland-Hawthorn et al 1998), which would produce significant variations in Hα intensity from cloud to cloud and even within a cloud.…”
Section: Discussion and Future Workmentioning
confidence: 48%
See 1 more Smart Citation
“…Several HVCs with strong direct distance constraints (see Wakker 2001 for a summary) have now been detected in H by WHAM (TRH98), Weiner et al (2001), and this survey. There is also an IVC (complex K; Haffner, Reynolds, & Tufte 2001) that has been completely mapped in H emission and has a distance constraint. The H emission measures from these clouds are …”
Section: The H Distance Constraintmentioning
confidence: 99%
“…S is not depleted (Savage & Sembach 1996b and references therein), and its second ionization potential of 23.3 eV is high enough to ensure that S ii is the dominant ion in both neutral and partially ionized diffuse gas. From a study of H and [S ii] emission lines, Haffner et al (1999) find that typically S ii=S $ 0:3 0:8 in the WIM. We therefore have N (H i) þ N (H ii) ¼ (H=S) N (S ii), and thus we can derive the cooling rate per nucleon as…”
Section: Electron Density and Cmentioning
confidence: 99%